2020
DOI: 10.1111/age.12978
|View full text |Cite
|
Sign up to set email alerts
|

SNP‐based heritability and genetic architecture of cranial cruciate ligament rupture in Labrador Retrievers

Abstract: Summary Cranial cruciate ligament rupture (CCLR) is one of the leading causes of pelvic limb lameness in dogs. About 6% of Labrador Retrievers suffer from this orthopedic problem. The aim of this study was to determine the heritability of CCLR in this breed using SNP array genotyping data. DNA samples were collected from CCLR‐affected dogs (n = 190) and unaffected dogs over the age of 8 years (n = 143). All 333 dogs were genotyped directly or imputed up to approximately 710k SNPs on the Affymetrix Axiom Canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Body weight was 40:4 ± 11:8 kg (range 26.6-64 kg, median 37.3 kg). Breeds studied were mixed breed (2), Labrador Retriever (2), German Shepherd Dog (2), English Springer Spaniel (1), Newfoundland (2), Pit Bull Terrier (1), Golden Retriever (1), Rottweiler (1), and Bernese Mountain Dog (1).…”
Section: Resultsmentioning
confidence: 99%
“…Body weight was 40:4 ± 11:8 kg (range 26.6-64 kg, median 37.3 kg). Breeds studied were mixed breed (2), Labrador Retriever (2), German Shepherd Dog (2), English Springer Spaniel (1), Newfoundland (2), Pit Bull Terrier (1), Golden Retriever (1), Rottweiler (1), and Bernese Mountain Dog (1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have identified a narrow femoral intercondylar notch, increased inflammatory cytokine production by synovial cells, and poor blood supply to the ligament core as factors contributing to CCL degeneration; other risk factors include increased bodyweight/obesity, neuter status, age and breed (Comerford and others 2011, Kyllar and Čížek 2018, Kuroki and others 2019, Santarossa and others 2020). Heritability indices have been reported for Newfoundlands (0.27) and Labrador retrievers (0.48 to 0.886) (Wilke and others 2006, Baker and others 2017, Cook and others 2020).…”
Section: Figurementioning
confidence: 98%
“…Cranial cruciate ligament (CCL) rupture is one of the most frequent causes for pelvic limb lameness in dogs (1) posing substantial economical and clinical consequences (2). The origin and development of CCL disease has been widely discussed in many studies (3)(4)(5)(6)(7)(8). Currently, a variety of surgical treatment options have been developed, with Tibial Plateau Leveling Osteotomy (TPLO) and Tibial Tuberosity Advancement (TTA) being well established and frequently used surgical procedures (9,10).…”
Section: Introductionmentioning
confidence: 99%